Crystal Methamphetamine Use in Sexual Settings Among German Men Who Have Sex With Men - Schecke, Henrike; Lea, Toby; Bohn, Annette; Köhler, Thorsten; Sander, Dirk; Scherbaum, Norbert; Deimel, Daniel (Frontiers in Psychiatry, 2019)
Introduction: Men who have sex with men (MSM) are a vulnerable subgroup for problems with substance use, including crystal methamphetamine. Drug use in sexual settings, commonly referred to as “chemsex”, has been an issue of growing concern in MSM communities. Recreational drugs commonly associated with “chemsex” include crystal methamphetamine, GHB/GBL, mephedrone, and ketamine. Drug use in sexual settings is correlated with sexual practices associated with the acquisition and transmission of sexually transmitted infections, including HIV and hepatitis C. Adverse mental health outcomes are often reported at higher rates among MSM who use methamphetamine. Methods: This paper refers to a subset of participants from the “German Chemsex Survey”, a MSM-community recruited, self-completed online survey with a self-selected convenience sample. Participants who used crystal methamphetamine for sex (n=130) were compared to participants who did not use drugs for sex (n=177). The survey comprised 420 different items considering recreational substance use, substance use in sexual settings, harm reduction strategies, mental health, sexual transmitted infections and mental health care service utilization. Results: A total of 1583 men started the survey, 1050 participants provided information on substance use. Twenty-seven percent of participants used crystal methamphetamine in the last 12 months, and of those, 89% used methamphetamine in a sexual setting and 50% reported injecting methamphetamine. Regarding mental health, participants who reported methamphetamine use in sexual settings were more likely to report symptoms of depression, somatization, anxiety and PTSD than the German male general population. Participants who reported methamphetamine use for sex were more likely to report symptoms of major depression, being HIV-positive and taking HIV pre-exposure prophylaxis (PrEP) than participants who did not report methamphetamine use. Most participants used harm reduction practices to reduce the risks associated with using methamphetamine in sexual settings. Conclusion: Crystal methamphetamine is used in the context of sexual activities by German MSM. Poorer mental health status than in the male general population was observed. MSM who used methamphetamine in this study seemed to be aware of potential health risks associated with their substance use and utilized harm reduction strategies and biomedical HIV-prevention strategies like PrEP.